Conductivity Transport Mechanisms of Solution-Processed Spinel Nickel Cobaltite-Based Hole Transporting Layers and Its Implementation as Charge Selective Contact in Organic Photovoltaics - Apostolos Ioakeimidis; Aristeidis Kottaras; Dimitrios Karageorgopoulos; Efstathia Christia; Sotirios Sakkopoulos; Evangelos Vitoratos; Stelios A. Choulis; Ioannis T. Papadas (Environmental Sciences Proceedings, 2023)
The electrical properties of solution-processed spinel nickel cobaltite (NiCo2O4) nanoparticulated-based metal oxide hole transporting layers are investigated using conductivity and Hall effect measurements. The mechanism of electrical conductivity of NiCo2O4-based electronic films as a function of temperature indicates hopping-type carrier transport. We show that NiCo2O4 hole transporting layers (HTLs) have suitable conductivity, low toxicity, and relatively low processing temperature, parameters that are important for electronic materials specifications of high performance and environmentally friendly emerging photovoltaics. As a proof of concept, NiCo2O4 and Cu-SCN surface-modified NiCo2O4 are incorporated as HTLs for non-fullerene acceptor Organic Photovoltaics (OPVs), and the photovoltaic performance results of the corresponding OPVs are presented.